TO STUDY THE CLINICAL AND DEMOGRAPHIC PROFILE OF COVID-19 PEDIATRIC PATIENTS (UP TO 18 YEARS) IN A TERTIARY CARE CENTER OF JAIPUR, RAJASTHAN - AGARWAL, SHEJAL; PARMAR, SHALIN; MARWAH, PRIYA; KAKKAR, MUNISH KUMAR; GUPTA, JITENDRA KUMAR; ABHISHEK KUMAR SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Coronavirus disease-19 (COVID-19) infection has quickly developed into a global pandemic. According to the available evidence, children appear to be less likely to be afflicted and the condition may be less severe, but things could change. Rapid deterioration and enhancements in the physiologic state are a hallmark of the pediatric community. Therefore, this study was conducted with the aim to study the demographic and clinical parameters of pediatric COVID patients. Methods: This hospital-based prospective and retrospective study was conducted during April 1st, 2020–July 2022 at the COVID ward and outpatient department, Mahatma Gandhi Medical College and Hospital, Jaipur. We included 276 children up to 18 years suffering from COVID-19 infection. We collected data of our study population from medical records and filled up the predesigned pro forma for admitted patients. Admitted children were classified as, per ICMR guidelines as: asymptomatic, mild, moderate, and severe variety. Statistical analysis was done with the SPSS software. Results: Highest percentage of cases 48.39% in the age group 12–18 years, were followed by 31.45% in the 7–12-year-old age group. About 13.04% of patients were asymptomatic, whereas the remaining cases were symptomatic, with severity levels of mild 49.28%, moderate 26.81%, and severe 10.87%. Fever was the most prevalent symptom 69.2%, cough at 43.84%, throat ache 18.12%, breathing difficulties 15.22%, headache 2.54%. Conclusion: In the present study, we concluded that during the third wave of the pandemic, most children had symptomatic illnesses, but recovery was fast among non-hospitalized children. Multisystem inflammatory syndrome in children was more common in elderly children.